(untitled) (CAHIERS MAGELLANES-NS, 2024)
The Code of Criminal Procedure, 1973 is a procedure code established for preventing crimes and helps to get remedies to the aggrieved party. It is a procedural law that provides a systematic procedure to the substantive criminal laws so that these laws come into force efficiently. In this new era of technologies, crimes have been committing through various cyberspace, and our Criminal Procedure Code and Indian Penal Code needs to be efficient for preventing those crimes. The Code of Criminal Procedure, 1973 has numerous amendments by parliament as per the societal needs. Recently, the Code has been replaced by Nagarik Suraksha Sanhita to match the contemporary era which became operative from July, 2024. In India, due to a lack of proper investigation tools and procedural delay now 44 million cases are pending in all the courts of India. Indian Justice System governs by Dicey’s ‘Rule of Law’ through which we can get a fair and just procedure trial hence we are bound by basic tenets of the justice system so before amending any Act or Statute, parliament needs to take care of these principles. In 2022 parliament passed one of the controversial and unique amendment through parliamentary proceedings which bring a new amendment in The Code of Criminal Procedure Act known as The Criminal Procedure Code (Identification) Act 2022. This amendment adopts for having better investigation technologies in order to solve the cases successfully which will helps to have easy disposal of cases. Though this paper author trying to present a critical analysis of this bill which includes international legal perspective related to identification of prisoners, overview of The Identification of Prisoners Act, 1920 and The Criminal Procedure Code (Identification) Act, 2022 Amendment effects on Part III of the Constitution and merits and demerits of the new CRPC Amendment Act 2022, The probable impacts of the society this new CRPC Amendment Act, 2022 intense to bring.